2021
DOI: 10.9770/jesi.2021.9.2(34)
|View full text |Cite
|
Sign up to set email alerts
|

Success from the perspective of female entrepreneurs

Abstract: The research in the field of entrepreneurial activity is increasing. In addition to classical economic definitions, researchers are trying to capture this phenomenon in subjective terms. Some research focuses on the fact that female entrepreneurs cannot be examined purely on the basis of economic factors, since subjective factors are in many cases more important for women. Within the framework of this study, we are trying to define how female entrepreneurs in Slovakia interpret the concept of success, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Studies focusing on female entrepreneurship emphasise the importance of subjective factors, arguing that they seem to be even more important than economic indicators, in the case of women (Gódány -Mura 2021). However, studies show that the motivations, goals and aspirations of entrepreneurs, regardless of gender, tend to extend beyond monetary returns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies focusing on female entrepreneurship emphasise the importance of subjective factors, arguing that they seem to be even more important than economic indicators, in the case of women (Gódány -Mura 2021). However, studies show that the motivations, goals and aspirations of entrepreneurs, regardless of gender, tend to extend beyond monetary returns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is necessary to realize that without knowing the risks, it is not possible to develop a strategic plan (Wallis 2020). Analysis of strategic risks works only if it is supported by strategic management; a properly performed analysis improves management of corporate processes and minimizes negative effects on labor efficiency and other corporate activities (Walaszczyk 2016;Virglerova et al 2020;Godany, Mura 2021). Man, Radu and Tabor (2015) and Pour et al (2019) state that there are many factors affecting strategic risk analysis, and they believe that factors associated with the highest risk include particularly human resources.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Meanwhile, the study of Godany and Mura (2021) showed that, besides objective factors directly related to economic ones, subjective factors, such as non-economic goals, are important factors in the success of entrepreneurial activities led by women. According to this study, the independence gives female entrepreneurs the opportunity to have free time and therefore be able to perform their family responsibilities more flexibly (Godany and Mura 2021).…”
Section: Introductionmentioning
confidence: 99%